2022
DOI: 10.1021/acsanm.1c03975
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Modification of ZSM-5-Encapsulated Uniform Pt Nanoparticles for Catalytic Oxidation of Volatile Organic Compounds

Abstract: Zeolite-supported noble-metal catalysts are considered to be one of the most promising materials to achieve complete oxidation of volatile organic compounds (VOCs). However, noble metals tend to agglomerate under synthesis/reaction conditions and are easily poisoned by halogen compounds, resulting in reduced catalytic activity and stability. Herein, Pt nanoparticles (∼2 nm) encapsulated in ZSM-5 catalysts (Pt/Z-En) with a series of Si/Al molar ratios were prepared by a one-pot synthesis strategy using tetraamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Although transition-metal oxides like MnO 2 and CeO 2 exhibit HCHO oxidation activity, the performance is too low at room temperature . Till date, noble metal nanoparticles, especially Pt, are the most active for HCHO oxidation at room temperature. , Ji and co-workers developed Pt nanoparticles supported on ZSM-5 and ZnO-modified TiO 2 arrays, over which 95% HCHO conversions were obtained at 303 K for 100 h. , 0.8% Pt/Fe 3 O 4 catalyst completely oxidized 1 ppm HCHO/air at a space velocity of 150 L/(gh) and converted 70% HCHO of 100 ppm HCHO/air at a higher space velocity of 600 L/(gh) at room temperature …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although transition-metal oxides like MnO 2 and CeO 2 exhibit HCHO oxidation activity, the performance is too low at room temperature . Till date, noble metal nanoparticles, especially Pt, are the most active for HCHO oxidation at room temperature. , Ji and co-workers developed Pt nanoparticles supported on ZSM-5 and ZnO-modified TiO 2 arrays, over which 95% HCHO conversions were obtained at 303 K for 100 h. , 0.8% Pt/Fe 3 O 4 catalyst completely oxidized 1 ppm HCHO/air at a space velocity of 150 L/(gh) and converted 70% HCHO of 100 ppm HCHO/air at a higher space velocity of 600 L/(gh) at room temperature …”
Section: Introductionmentioning
confidence: 99%
“…5 Till date, noble metal nanoparticles, especially Pt, are the most active for HCHO oxidation at room temperature. 6,7 Ji and co-workers developed Pt nanoparticles supported on ZSM-5 and ZnOmodified TiO 2 arrays, over which 95% HCHO conversions were obtained at 303 K for 100 h. 8,9 0.8% Pt/Fe 3 O 4 catalyst completely oxidized 1 ppm HCHO/air at a space velocity of 150 L/(gh) and converted 70% HCHO of 100 ppm HCHO/ air at a higher space velocity of 600 L/(gh) at room temperature. 2 Numerous studies have reported the influences of support shapes for reactions and revealed the dependence of catalytic performance on the exposed crystal planes of the shaped support.…”
Section: Introductionmentioning
confidence: 99%
“…20 For example, Zhu et al prepared Pt NPs encapsulated in ZSM-5 catalysts (Pt/Z-En) with a series of Si/ Al molar ratios involving one-pot synthesis method and using tetraammineplatinum nitrate as the metal precursor. 21 The results confirmed that the Pt−zeolite interaction and metal dispersion were significantly enhanced after metal encapsulation in zeolite. Chai et al have developed an efficient in situ strategy for encapsulation of Pd nanoparticles within MFI-type zeolites using (3-mercaptopropyl)trimethoxysilane as a ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Different ligands, such as ammonia, ethylenediamine, and mercaptosilane, were previously introduced to the synthesis mixture . For example, Zhu et al prepared Pt NPs encapsulated in ZSM-5 catalysts (Pt/Z-En) with a series of Si/Al molar ratios involving one-pot synthesis method and using tetraammineplatinum nitrate as the metal precursor . The results confirmed that the Pt–zeolite interaction and metal dispersion were significantly enhanced after metal encapsulation in zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites with MFI, FAU and BEA codes-supported metal catalysts are one of the most promising materials to achieve oxidation of air pollutants [6][7][8][9]. These solids have well-established applications as supports and catalysts because of their beneficial properties including, a high specific surface that promotes the high dispersion of the active sites and well-defined pore structure with channels and cavities able to encapsulate nanoparticles (NPs) and reduce sintering effects, ion exchange ability, and thermal and hydrothermal stability [10].…”
Section: Introductionmentioning
confidence: 99%